The efficacy of arterial only microsurgical nasal replantation: a systematic review - Secanho, Murilo Sgarbi; Rajaram, Rohan; Menezes Neto, Balduino Ferreira de; Cavale, Naveen; Ng, Sally Kiu‐Huen; Palhares Neto, Aristides Augusto (Wiley, 2024)
BACKGROUND: Microsurgical nasal replantation is a rare yet important procedure in order to regain the respiratory, olfactory, and aesthetic features of the nose. However, due to the traumatic nature of most nasal amputations, appropriate veins for anastomosis are difficult to find- complicating replantation. This is the first systematic review that compares peri operative and post-operative outcomes in arterial only versus arterial and venous anastomosis for nasal replantation. METHODS: A comprehensive search of Medline, SCOPUS, and Embase databases up to 30th November 2023 was undertaken. Inclusion criteria included studies reporting on nasal replantation. Reports were then split into venous anastomosis and arterial only anastomosis and compared against one another. The Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Case Reports tool was used for bias assessment. Comparative analysis was undertaken using Microsoft Excel software utilizing chi squared tests and t-tests where necessary. RESULTS: A total of 27 papers with a sample size of 29 were found. Risk of bias for the included studies was generally low. Demographics between the two groups were similar. Arterial only anastomosis was on average 2 h and 32 min faster. Arterial only anastomosis utilized Hirudotherapy (medicinal leeching) more often than venous anastomosis (P = 0.01) whereas venous anastomosis used heparin more frequently (P = 0.01). Otherwise, complications, tissue preservation, hospital stay and follow up outcomes were similar between the two groups. CONCLUSION: The evidence to date suggests that arterial only anastomosis is a safe and viable method for nasal replantation.